2022
DOI: 10.48077/scihor.24(9).2021.19-25
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Composition of Whey and Cottage Cheese Under Various Rennet Enzymes

Abstract: Rennet cheeses occupy an important place in the diets of the population of Ukraine. The technology of making cheeses depends on both the quality of raw materials and the quality of enzymes that are used to curdle milk. Therefore, the study of the effect of rennet enzymes obtained using advanced biotechnology on the transformation of milk protein and amino acids into a finished product is of scientific and practical importance. Considering the above, the purpose of this study was to investigate the amino acid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…L-phenylalanine is a precursor of phenylacetaldehyde and 2-phenylethanol-compounds that were characterized by the highest OAVs in the aroma produced by G. geotrichum on substrates with by-products of the dairy industry [12,13,26]. It is an amino acid present in sour whey and is additionally supplemented with the substrate to ensure the possibility of its bioconversion to the highest possible concentration of honey and rose aroma compounds [30]. The results of the amino acid analysis showed that during the fermentation process of the medium with sour whey almost all L-phenylalanine was metabolized, with a radical decrease in its concentration on the last day of cultivation.…”
Section: Amino Acid Concentration During Biotransformation Of Sour Wh...mentioning
confidence: 99%
“…L-phenylalanine is a precursor of phenylacetaldehyde and 2-phenylethanol-compounds that were characterized by the highest OAVs in the aroma produced by G. geotrichum on substrates with by-products of the dairy industry [12,13,26]. It is an amino acid present in sour whey and is additionally supplemented with the substrate to ensure the possibility of its bioconversion to the highest possible concentration of honey and rose aroma compounds [30]. The results of the amino acid analysis showed that during the fermentation process of the medium with sour whey almost all L-phenylalanine was metabolized, with a radical decrease in its concentration on the last day of cultivation.…”
Section: Amino Acid Concentration During Biotransformation Of Sour Wh...mentioning
confidence: 99%
“…Одним із найважливішим компонентом молока є білки, що представлені в своїй основі казеїном і сироватковими білками. З хімічної точки зору білки -це високомолекулярні сполуки, що складаються з амінокислот [14]. У функціональній діяльності організму амінокислоти виконують субстратну і регуляторну функції в біосинтезі білка, активно включаються в енергетичні процеси, є джерелом фізіологічно активних амінів, беруть участь в утворенні нуклеїнових кислот, ліпідів, гормонів [15,17].…”
Section: вступunclassified
“…Acid composition is an important indicator of dairy products and characterizes their biological value (Bilyi et al, 2021;Bily & Merzlov, 2022). The physiological value of such amino acids is diverse, for example, lysine helps to increase the level of hemoglobin in the blood and the body's assimilation of phosphorus, calcium, and iron (Merzlov, 2019).…”
Section: Introductionmentioning
confidence: 99%